2010
DOI: 10.1292/jvms.09-0377
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies against Transmissible Gastroenteritis Virus and Porcine Respiratory Coronavirus among Pigs in Six Regions in Japan

Abstract: ABSTRACT. A total of 2,703 pig sera from 171 farms in six regions in Japan were screened for virus-neutralizing (VN) antibody against transmissible gastroenteritis virus (TGEV). Although none of the farms had clinical signs of transmissible gastroenteritis (TGE) or vaccination against TGEV, VN antibody was detected in 14.4% of sera at 30 farms (17.5%) across all six regions. On testing of 263 VN antibody-positive sera from 27 farms with a commercial blocking ELISA to distinguish TGEV and porcine respiratory co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…This difference is recognized minimal at the genetic level, which explains how both viruses are considered as one species Alphacoronavirus 1 (Lin et al, 2015), but it can be great phenotypically, as it may be the result of their different tissue tropism, as the expressed S glycoprotein is responsible for cell entry (Ballesteros, Sanchez, & Enjuanes, 1997). In contrast to TGEV, PRCV has respiratory tropism and usually causes an undiscerned subclinical infection (Pensaert, Cox, Van Deun, & Callebaut, 1993), which can induce the production of cross-reacting antibodies, causing difficulties in serological diagnostics (Miyazaki, Fukuda, Kuga, Takagi, & Tsunemitsu, 2010). The virus neutralization assay cannot be used to differentiate TGEV and PRCV, therefore various enzyme-linked immunosorbent assays (ELISA) were developed using monoclonal antibodies targeting the different epitopes of the S protein (Carman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This difference is recognized minimal at the genetic level, which explains how both viruses are considered as one species Alphacoronavirus 1 (Lin et al, 2015), but it can be great phenotypically, as it may be the result of their different tissue tropism, as the expressed S glycoprotein is responsible for cell entry (Ballesteros, Sanchez, & Enjuanes, 1997). In contrast to TGEV, PRCV has respiratory tropism and usually causes an undiscerned subclinical infection (Pensaert, Cox, Van Deun, & Callebaut, 1993), which can induce the production of cross-reacting antibodies, causing difficulties in serological diagnostics (Miyazaki, Fukuda, Kuga, Takagi, & Tsunemitsu, 2010). The virus neutralization assay cannot be used to differentiate TGEV and PRCV, therefore various enzyme-linked immunosorbent assays (ELISA) were developed using monoclonal antibodies targeting the different epitopes of the S protein (Carman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although we have no direct proof of this assumption, namely that the presence of PCV is responsible for the TGEV problem, serological results (Table 1) showed that primiparous pigs may remain seronegative for both TGEV and PRCoV. Similar increases of TGE incidence have been reported from Japan (Miyazaki et al, 2010) and China (Wang et al, 2013), the world's largest pork producer.…”
Section: Discussionmentioning
confidence: 71%
“…However, occasional reports of TGEV-specific seropositivity (Elvander et al, 2000;Brendtsson et al, 2006;Roic et al, 2012) and even sporadic outbreaks in different parts of the world (Pritchard et al, 1999;Kim et al, 2000;Miyazaki et al, 2010;Wang et al, 2010) indicate that TGE cannot be neglected, as the virus is still present in pig herds, although mostly without clinical manifestations.…”
Section: Lőrincz Et Almentioning
confidence: 99%
“…Despite the availability of commercial vaccines, TGE still poses a regional threat to the swine industry due to the high morbidity and mortality that TGEV causes in suckling piglets under 2 weeks of age (Miyazaki et al, 2010). Although passive, lactogenic immunity induced by virulent or attenuated TGEV vaccines can provide effective protection, sufficient risk remains.…”
Section: Discussionmentioning
confidence: 99%
“…Three experimental approaches were used to evaluate the antiviral activity of pepTGEV-M7 (Miyazaki et al, 2010;Ren et al, 2011b). First, to assess the ability of the peptide to bind TGEV in vitro, 100 TCID50 of TGEV was pre-incubated with pepTGEV-M7 at 500, 250, 125, 62.5 or 31.25 lg/ml before infecting ST cells.…”
Section: Antiviral Activity Of Peptgev-mmentioning
confidence: 99%